The Role of Trust in Mediating E-Service Quality on Repurchase Intention Among Shopee Customers in Denpasar City - Anak Agung Ngurah Kameshwara Mahottama; I Gst. Ayu Kt. Giantari (Institut Teknologi dan Bisnis (ITB) Semarang, 2025)
The Global Web Index indicates that online store visits account for 91 percent of internet users in Indonesia. People tend to use the internet to search for products or services to purchase online. Online transactions have now become a trend among the public. According to a report by Google, Temasek, and Bain & Company, the gross merchandise value (GMV) of e-commerce marketplaces in Indonesia is estimated to reach US62 billion, or approximately IDR 982.76 trillion, in 2023, reflecting a 7 percent growth from the previous year. E-service quality is increasingly recognized as a crucial aspect and a key factor in determining the competitive advantage of online businesses. Trust is defined as one party’s confidence in a relationship and the belief that the actions taken will be in their best interest, resulting in positive outcomes for the trusted party. This study aims to examine and explain the role of trust in mediating the effect of e-service quality on customers' repurchase intention. The research was conducted on Shopee customers in Denpasar City, with a sample size of 100 respondents obtained through non-probability sampling methods. Data were collected using questionnaires. The analytical techniques employed in this study included path analysis with SPSS, the Sobel test, and the Variance Accounted For (VAF) test. The results of the analysis indicate that: E-service quality has a positive and significant effect on customers' repurchase intention; E-service quality has a positive and significant effect on customers' trust; Trust has a positive and significant effect on customers' repurchase intention; Trust successfully mediates the effect of e-service quality on customers' repurchase intention.